Legal Form as a Determinant of the Evaluation of Agricultural Entities in Slovakia Using the Topsis Method - KRAVČÁKOVÁ VOZÁROVÁ, Ivana; KOTULIC, Rastislav; VAVREK, Roman (Journal of Environmental Management and Tourism, 2016)
The agriculture represents one of the sectors of the economy, where economic differentiation is more than obvious. Different efficiency of agricultural entities has been a persistent phenomenon that depends on several objective and subjective factors. One of them is also legal form of agricultural enterprises. In Slovakia, the structure of farms is specific compared to almost any other member states of the European Union. The majority of agricultural land is framed by big farms. These farms with high acreage are usually either agricultural cooperative or Business Company. In the economic literature is a number of important studies identifying the advantages of cooperatives in comparison with other organizational forms, mainly business companies. The aim of this paper is evaluate the economic status of agricultural entities according the legal form using the TOPSIS method.
Keywords: business company; agricultural cooperative; legal form; TOPSIS method